Gender Differences in Social Media Engagement and Its Psychological Consequences: A Sociological Study of Undergraduate University Students in District Faisalabad - Dr. Madiha Naz; Sajid Hassan; Fouzia Mumtaz; Dr. Naveed Farah; Muhammad Asif Saddique; Areesh Abdul Ghafoor; Dr. Nouman Khaliq (Research Journal of Psychology, 2025)
Social media's widespread impact has changed how university students around the world communicate, collaborate academically, and interact with one another. However, there is still growing concern about the psychological effects of excessive engagement. Through a comparative analysis of gender and institutional context (public versus private universities), this quantitative study examines the psychological effects of social media use among undergraduate students in District Faisalabad, Pakistan. The study used correlation survey and sampled 200 undergraduate students from four institutions (two public and two private), evenly distributed by gender and university type. Yamane's formula was used to determine the sample size. Survey instruments measuring the degree of social media engagement, psychological distress (as measured by validated anxiety and depression scales), and academic stress were used to gather data. To examine the effects of social media usage, gender, and institutional type on psychological outcomes, descriptive and inferential statistical techniques such as two-way ANOVA, independent samples t-tests, were employed. Results showed that, in comparison to their male peers, female students frequently reported higher levels of psychological distress, emotional exhaustion, and anxiety related to social media use. Furthermore, students at private universities used social media more intensely and suffered from much worse psychological effects than those at public universities. The most vulnerable subgroup, according to interaction effects, was female students at private universities, who showed the highest levels of distress across all psychological measures. This study emphasizes how crucial it is to place the psychological effects of social media within the intersecting frameworks of institutional affiliation and gender. In higher education settings, the findings urge the adoption of institution-specific digital literacy programs, gender-sensitive mental health services, and evidence-based digital wellness initiatives. These interventions are essential for reducing the negative impacts of social media and creating more positive learning and psychological environments for students in Pakistan and similar situations around the world.